2018
DOI: 10.1242/jcs.210492
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid – an anti-angiogenic phytohormone that modulates the phenotypical plasticity of endothelial cells and macrophages

Abstract: Abscisic acid (ABA) has shown anti-inflammatory and immunoregulatory properties in preclinical models of diabetes and inflammation. Herein, we studied the effects of ABA on angiogenesis, a strictly controlled process that, when dysregulated, leads to severe angiogenic disorders including vascular overgrowth, exudation, cellular inflammation and organ dysfunction. By using a 3D sprouting assay, we show that ABA effectively inhibits migration, growth and expansion of endothelial tubes without affecting cell viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Since our studies showed that the interplay among CCN1 signaling, cytoskeletal architecture, and YAP transcriptional activation normalizes angiogenesis in the retina, we postulated that they could serve as potential molecular tools to correct vascular abnormalities. Therefore, we investigated the functional relevance of CCN1-YAP cross talk in pathological angiogenesis using mice with oxygen-induced retinopathy (OIR), a model of ischemia-induced VEGF-dependent retinal neovascularization (32,33). Mice were subjected to hyperoxia from P7 to P12 to induce vaso-obliteration and normoxia until P17 to produce maximal preretinal neovascularization ( Fig.…”
Section: Figmentioning
confidence: 99%
“…Since our studies showed that the interplay among CCN1 signaling, cytoskeletal architecture, and YAP transcriptional activation normalizes angiogenesis in the retina, we postulated that they could serve as potential molecular tools to correct vascular abnormalities. Therefore, we investigated the functional relevance of CCN1-YAP cross talk in pathological angiogenesis using mice with oxygen-induced retinopathy (OIR), a model of ischemia-induced VEGF-dependent retinal neovascularization (32,33). Mice were subjected to hyperoxia from P7 to P12 to induce vaso-obliteration and normoxia until P17 to produce maximal preretinal neovascularization ( Fig.…”
Section: Figmentioning
confidence: 99%
“…This study indicates that retinoic acid improves healing process through its stimulatory effect on macrophages. Chaqour, Lee, Ravichandra, and Chaqour () studied the effect of abscisic acid (ABA)—a plant hormone (involved in plant stress response and plant buds dormancy) on the retinal and fetal angiogenesis, using a 3D sprouting assay methodology in retinal vasculature mice model. They showed that ABA inhibits development and regeneration of blood vessels and speeds up macrophage‐induced programmed regression of fetal blood vessels.…”
Section: Promotion Of Cell Proliferation Angiogenesis and Productiomentioning
confidence: 99%
“…Anti-VEGF strategies, which include neutralization by engineered antibodies, chimeric receptors, or laser treatment that alleviates ischemia, an important stimulus for VEGF expression, have been proposed as promising therapies [15,27]. Although partially effective, several side adverse effects have been associated with anti-VEGF agents, including visual impairment since this growth factor has also been shown to have neuroprotective functions in the survival of retinal ganglion cells [28].…”
Section: Ischemic Retinopathies (Irs)mentioning
confidence: 99%
“…At the moment, there is almost no literature about the direct functional effects of ABA in this neurosensorial tissue. However recently, Chaqour and coworkers have studied the effects of ABA administration on physiological and pathological angiogenesis processes in the retina, particularly in a mouse model of OIR [27]. Interestingly, they showed that this phytohormone acts largely by altering the phenotypical plasticity of endothelial cells and skewing the canonical polarized inflammatory statuses of macrophages towards an antiangiogenic phenotype.…”
Section: Aba As a Novel Therapy For Irsmentioning
confidence: 99%
See 1 more Smart Citation